Picturesque Trinidad - Rice, Ben (Unknown, 2011)
The postcard shows a view of the coast of Trinidad. The addressee name on the postcard is unclear, but the postcard was mailed to Connecticut, United States of America and dated 1911.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; 1911; Bays--Trinidad and Tobago; Bodies of water--Trinidad and Tobago; Seas--Trinidad and Tobago; Mountains--Trinidad and Tobago